The institution of popular veto: experience of selected foreign countries - Маріола Міровська (Конституційно-правові академічні студії, 2024)
This article examines the legislation of foreign countries regarding mechanisms of direct democracy, particularly the institution of popular veto. A historical analysis of the development of this instrument in European law has been conducted.